Study of the Space Occupied by a Wheelchair User at Metro de Santiago Platforms by Laboratory Experiments - Joaquin Valdivieso; Sebastian Seriani (Journal of Advanced Transportation)
The objective is to study the space a wheelchair passenger would use in the preferential waiting areas of an urban railway platform. For this purpose, an analysis of the variables that interfere in the space occupied by a wheelchair user was carried out at Metro de Santiago platforms, to design a preferential prototype waiting area at the Human Dynamics Laboratory of the Universidad de los Andes (Chile). The prototype has a 3.0 m long and 2.5 m wide carriage, together with a preferential waiting area on the platform of the same length as the carriage, and 2.0 m wide. With this prototype defined, a detection method was developed using PeTrack software, to accurately identify the limits of the space occupied by a wheelchair user under two scenarios of different density levels in the preferential waiting area: medium-density (1.5 passengers/m2) and high-density (4.0 passengers/m2). It was observed that the space occupied by a wheelchair user decreased by 33% as the density increased from medium to high. On the other hand, for a high-density level, the space occupied by a wheelchair user was found to be 61% higher than that occupied by a passenger without reduced mobility. This variation occurred mainly because passengers increased their distance from the wheelchair user, which widened their area of influence. Further experiments are proposed as future research to extend this analysis using other density situations.